THE EFFECTIVENESS OF THE ACUPUNCTURE REDUCING POINT ON THE IMPROVEMENT OF MUSCULAR STRENGTH OF STROKE PATIENTS - Hartono, Dodik; Prasetyanto, Deny; Salam, Ainul Yaqin; Handayani, Erna; Sriyono, Grido Handoko; Ishaq, Ishaq; Tonny, Harry Irfan (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Stroke is a disease caused by disruption of blood flow to areas of the brain that are blocked in the cerebral or cervical arteries which result in decreased or even loss of function controlled by brain tissue. One of the effects caused by stroke is hemiparesis. Rehabilitation therapy plays an important role in a comprehensive restoration of bodily functions due to stroke, this program aims to restore function to reduce disability, one of the treatments is to use acupuncture meridian points. Purpose: The purpose of this study was to determine the effectiveness of acupuncture meridian points in increasing muscle strength in stroke patients. Methods: The research design used in this study was a randomized controlled trial (RCT) design. The number of samples of all stroke patients at the Holistic nursing therapy clinic in Probolinggo and the Healer School Jember Clinic that met the inclusion criteria from October 2020 to March 2021 were 270 respondents. Data collection techniques used observation sheets to assess muscle strength before and after the intervention of acupuncture meridian points in stroke patients. Data analysis used was the Wilcoxon test with a statistical significance value accepted if p <0.05. Results: The results of the data analysis of the intervention group showed a significant value of hand muscle strength (p 0.003; α 0.05) and leg (p 0.005, α 0.05) where (p <0.05) it can be concluded that there is a significant difference in strength. A muscle in the intervention group before and after being given acupuncture. The findings of this study suggest that there is a significant effect of acupuncture on lower and upper muscle strength. Conclusion: In general, the use of acupuncture meridian points can increase muscle strength in stroke patients, so the use of acupuncture meridian points can provide benefits for restoring muscle strength in stroke patients.